Adipose tissue macrophages: unique polarization and bioenergetics in obesity - Caslin, Heather L. (Immunol Rev, 2020)
Macrophages comprise a majority of the resident immune cells in adipose tissue (AT) and regulate both tissue homeostasis in the lean state and metabolic dysregulation in obesity. Since the AT environment rapidly changes based upon systemic energy status, AT macrophages (ATMs) must rapidly adapt phenotypically and metabolically. There is a distinct dichotomy in the polarization and bioenergetics of in vitro models, with M2 macrophages utilizing oxidative phosphorylation (OX PHOS) and M1 macrophages utilizing glycolysis. Early studies suggested differential polarization of ATMs, with M2-like macrophages predominant in lean AT and M1-like macrophages in obese AT. However, recent studies show that the phenotypic plasticity of ATMs is far more complicated, which is also reflected in their bioenergetics. Multiple ATM populations exist near the middle of the M2 to M1 continuum and appear to utilize both glycolysis and OX PHOS in obesity. The significance of the dual fuel bioenergetics is unclear and may be related to an intermediate polarization, their buffering capacity, or the result of a mixed population of distinct polarized ATMs. Recent evidence also suggests that lean ATMs serve as a substrate buffer or reservoir to protect the AT from lipid, catecholamine, or iron overload. Furthermore, recent models of weight loss and weight cycling reveal additional roles for ATMs in systemic metabolism. Evaluating ATM phenotype and intracellular metabolism together may more accurately illuminate the consequences of ATM accumulation in obese AT, lending further insight into obesity related comorbidities in humans.